A DNA-Cleaving Molecule as a Diagnostic Biosensor for Clostridioides Difficile Infection - Chow, Kristie (My University, 2024)
Clostridioides difficile (CD) is a Gram-positive and anaerobic pathogen that is responsible for causing CD infection (CDI), which can lead to a spectrum of mild to life-threatening conditions. Current detection methods for CDI exhibit limitations, such as long turnaround time and sub-optimal sensitivity and specificity. Hence, a new molecular tool for detecting CD is needed. The development of in vitro selection technique has enabled the isolation and use of functional deoxyribonucleic acids (DNAs) as a molecular recognition element (MRE) for different biosensing applications. Particularly, a type of functional catalytic DNAs called fluorogenic RNA-cleaving DNAzymes (RFDs) are often used as a biosensor for bacterial detection due to their excellent specificity and sensitivity and adaptability to various signal transduction platforms. The project described here is aimed to develop and characterize RFDs that can recognize a major epidemic strain of CD. Herein, we performed an in vitro selection to select for CD-selective RFDs. Interestingly, we ended up isolating a DNA-cleaving molecule named DFM-CD1 that exhibits a DNA-cleaving nature and is cleaved at cytosine (C) dinucleotide junction. More intriguingly, trans-acting DFM-CD1 named DFT1 produces multiple cleavages at different CC dinucleotide junctions, a phenomenon that has not been reported in the research field of functional DNAs. After performing truncation and cleavage site mutations of DFT1, we successfully identified a truncated mutant, DT2M1c, that is single cleaving. DT2M1c is not only shorter but also exhibits an excellent sensitivity. This presents a compelling opportunity to employ DT2M1c as a MRE to develop the first electrochemical sensor for CDI, providing a novel and simple-to-use diagnostics in face of this threatening disease.
Keywords: Functional nucleic acids; Diagnostics; Biosensor; Clostridioides difficile infection